2023
DOI: 10.1186/s12933-023-01845-0
|View full text |Cite
|
Sign up to set email alerts
|

Liraglutide reduces plasma dihydroceramide levels in patients with type 2 diabetes

Abstract: Background Emerging evidence supports that dihydroceramides (DhCer) and ceramides (Cer) contribute to the pathophysiology of insulin resistance and liver steatosis, and that their circulating concentrations are independently associated with cardiovascular outcomes. Circulating DhCer levels are increased in patients with type 2 diabetes (T2D). On the other hand, the GLP-1 receptor agonist liraglutide reduces major adverse cardiac events, insulin resistance and liver steatosis in T2D patients. Th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
1
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(3 citation statements)
references
References 34 publications
2
1
0
Order By: Relevance
“…The findings presented here correspond well with previous studies on the effects of liraglutide and other GLP-1RAs on ceramides [ 12 , 51 54 ]. One study, on people with obesity ( n = 32), found that after one year of follow-up, those treated with liraglutide (1.2 mg/d) maintained a stable level of C16 Cer, whereas those without liraglutide treatment had an increase in the level of C16 Cer [ 52 ].…”
Section: Discussionsupporting
confidence: 92%
“…The findings presented here correspond well with previous studies on the effects of liraglutide and other GLP-1RAs on ceramides [ 12 , 51 54 ]. One study, on people with obesity ( n = 32), found that after one year of follow-up, those treated with liraglutide (1.2 mg/d) maintained a stable level of C16 Cer, whereas those without liraglutide treatment had an increase in the level of C16 Cer [ 52 ].…”
Section: Discussionsupporting
confidence: 92%
“…In this study, it was shown that RYR reduced the C-LDL level by 51%, and a statistically signi cant result was obtained in line with this study. In a study by Damien Denimal et al on liraglutide, it was evaluated that it signi cantly reduced the TyG index by 3.7% [11]. In this study, a statistically signi cant result was found in the liraglutide group, consistent with Damien Denimal et al's and other compared studies.…”
Section: Discussionsupporting
confidence: 88%
“…Total plasma ceramides did not significantly change after treatment, but species 18:0, 18:1, 19:0, 24:1 and 26:1 decreased significantly. The reduction in dihydroceramide after liraglutide was independently associated with reduced liver fat content (p=0.0005) and improved insulin resistance measured by the TyG index ( p -value=0.05) ( 140 ). Other studies exploring liraglutide’s impact in MASLD demonstrated the potential to down-regulate genes related to glycoceramide metabolism, prevent ceramide accumulation in cardiac progenitor cells, and offer anti-steatotic effects ( 151 ).…”
Section: Experimental/clinical Evidence Of Therapies Targeting Sphing...mentioning
confidence: 99%